Factors Associated with the Progression of Fibrosis on Liver Biopsy in Alaska Native and American Indian Persons with Chronic Hepatitis C - Stephen E Livingston; Heike Deubner; Dana L Bruden; Brian J McMahon; Chriss E Homan; Lisa J Townshend-Bulson; Michael G Bruce; Thomas W Hennessy; James L Williams; David R Gretch (Canadian Journal of Gastroenterology)
BACKGROUND: Various factors influence the development and rate of fibrosis progression in chronic hepatitis C virus (HCV) infection.